Lack of Effect of H2-Receptor Antagonists and Antacids on the Gastric and Duodenal Gastrin-, Somatostatin- and Serotonin-Producing Cells in Patients with Acid Peptic Disorders. (1st August 1996) - Yacoub, WR; Thomson, ABR; Hooper, P; Jewell, LD
Abstract : Standard therapeutic approaches to acid peptic disorders have dealt with neutralizing or inhibiting aggressive factors and/or bolstering defensive factors. Gastric and duodenal mucosal biopsies were examined from 90 patients with various acid peptic disorders, as follows: reflux esophagitis (n=24), gastric ulcer (n=13), duodenal ulcer (n=47) and nonulcer dyspepsia (n=6). Seven patients with minimal dyspeptic symptoms and an endoscopically and histologically normal stomach and duodenum served as controls. Immunoperoxidase staining for gastrin-producing G cells, somatostatin-producing D cells and serotonin-producing EC cells was carried out on fundic, antral and duodenal biopsies, and quantitated using a Zeiss MOP videoplan. No significant effects secondary to treatment with antacid, ranitidine or cimetidine were observed on endocrine cell densities and ratios. Biopsies obtained on different occasions over time indicated that in patients on enprostil (a synthetic E2 prostaglandin), there was a trend towards increasing cell counts, suggesting that the serum gastrin-lowering effect of this drug may result from inhibition of gastrin release. Thus, H2 -receptor antagonists and antacids do not alter gastric or duodenal mucosal G, D or EC cells in patients with acid peptic disorders.